An approach to torque ripple reduction in fully pitched switched reluctance motors by pole tip shaping - Garip, M; Ozoglu, Y; Mese, E (IEEE, 2002)
Torque ripple is a drawback for both conventional and fully pitched SRM structures. Although there are several publications in the literature addressing the full or partial solution to the problem for conventional SRM, but not for recently emerging fully pitched SRM. This paper proposes a solution to torque ripple problem in fully pitched SRM by shaping stator and rotor pole tips. The essence of the proposed method is to shape inductance profile of the motor so that torque profile changes accordingly. Analysis has been performed with the Finite Element (FE) model of 6/4 3-phase fully pitched SRM with unipolar excitation. Sharp increase and decrease in torque profile existing before proposed geometry has been smoothed out after pole tip shaping. This brings the torque ripple level from 37.2% to 13.7% for 6 A phase current.
Keywords: switched reluctance motor; fully pitched winding; unipolar excitation; torque ripple; Automation & Control Systems; Computer Science; Engineering; Telecommunications